A systematic review of using electrical stimulation to improve clinical outcomes after hip fractures. (2nd December 2022) - Davison, Paul; Wilkinson, Rianne; Miller, Jordan; Auais, Mohammad
ABSTRACT: Background: Pain and muscles weakness often delays regaining independent mobility following hip fracture surgery. Electrical stimulation may relieve pain and improve muscle strength and function. Purpose: To systematically review and evaluate available literature examining the effectiveness of using electrical stimulation to promote clinical outcomes after hip fractures. Methods: Two researchers independently searched MEDLINE, CINAHL, EMBASE, Web of Science, Cochrane Reviews, Physiotherapy Evidence Database, and PsycInfo from inception to July 1, 2018, with no restrictions. The quality and fidelity of the included interventions were assessed, and expert consultation was conducted to help explain the results. Results: We identified 432 records through database searching. Initial screening indicated 24 articles were appropriate for full-text review, and four articles met the inclusion criteria. In included studies, electrical stimulation (i.e. TENS) reduced pain (mean difference (MD) = 3.3 points on 10-point Visual Analogue Scale, p < .001), improved range of motion (ROM) (MD: 25.7°, p < .001), and accelerated functional recovery immediately after hip fracture ( p < .001). Conflicting evidence existed when using neuromuscular electrical stimulation to improve muscle strength and other functional outcomes (e.g. mobility); however, nine experts advised that longer-term interventions might be necessary to achieve significant improvment in muscle strength. Conclusion: Available evidence, albeit limited, supports the early application of noninvasive electrical stimulation (e.g. TENS) for improving clinical outcomes (i.e. reducing pain, improving ROM, and accelerating functional recovery after hip fractures). We could not find conclusive evidence on the effectiveness of using electrical stimulation to improve muscle strength. This review establishes the need for future additional high-quality trials in this field.